Comets and meteors - Asimov, Isaac, 1920-1992. (New York : Dell, 1990)
Discusses the characteristics of comets and meteors and cites both famous appearances and unexplained mysteries connected with them.
Includes index.
"Dell Yearling nonfiction."
Bibliography: p. 30.
Keywords: Comets -- Juvenile literature; Meteors -- Juvenile literature; Comets; Meteors